Penyuluhan dan Deteksi Dini Preeklamsia pada Ibu Hamil Berdasarkan Karakteristik di Rumah Sakit Setio Husodo - Butar-Butar, Armika Leora; Otana, Hotasi; Pohan, Atika (Cattleya Darmaya Fortuna, 2025)
Preeclampsia plays a role in intrauterine death and perinatal mortality. Preeclampsia is a risk factor for slow fetal growth, low birth weight (LBW), fetal dysmaturity and prematurity, and even intrauterine fetal death (IUFD). Mothers with preeclampsia will experience placental vascular dysfunction, which can disrupt blood flow to the placenta, thus preventing the fetus from optimally meeting its nutritional and oxygen needs. This condition results in delayed fetal growth (Prawirohardjo, 2016). In North Sumatra, 3,560 cases of preeclampsia were reported from 251,449 pregnancies in 2010, while at Dr. Pirngadi Medan reported that the maternal mortality rate for preeclampsia was 3.45% in 2007-2008, 2.1% in 2008-2009, and 4.65% in 2009-2010 (North Sumatra Health Office, 2011). A counseling session conducted at Setio Husodo Kisaran Regional Hospital in 2018 over a four-month period (April-June) found 34 mothers experiencing preeclampsia. Preeclampsia is hypertension that occurs after 20 weeks of gestation accompanied by proteinuria. Preeclampsia is followed by the onset of hypertension, proteinuria, and fever associated with pregnancy after 20 weeks of gestation or immediately after delivery (Walyani, 2016). The counseling results showed that pregnant women experiencing preeclampsia were categorized based on maternal age, with the majority aged <20 years (13 cases) and 38.4%. The majority of pregnant women with preeclampsia were primiparous (17 cases) and pregnant women with preeclampsia were primiparous (50%), and the majority of pregnant women with preeclampsia were in the third trimester (22 cases) (64.7%). Suggestions for managing preeclampsia in pregnant women include encouraging them to have regular prenatal checkups.